Philanthropic Washing in China: The Incongruence Between Corporate Social Responsibility and Image-Building Motives - Anwar M Radiamoda; Rizda Octaviani (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2025)
This study examines the phenomenon of “philanthropy washing” in China, defined as the use of philanthropic activities by companies to enhance their image without creating tangible social impact. The primary objective of this research is to explore how companies in China leverage corporate social responsibility (CSR) as a strategy to gain profit, increase consumer loyalty, and improve public reputation. Using a literature review approach, this study analyzes various reputable articles and journals examining the relationship between philanthropy and corporate image, as well as the social and political dynamics influencing it. The main findings indicate that although companies in China engage in philanthropic activities, these efforts often prioritize business interests over substantial social impact. The study also finds that political factors, institutional ownership, and pressures from the media and consumers play significant roles in shaping corporate philanthropy strategies. Nevertheless, this research acknowledges its limitations in terms of empirical data coverage and suggests further studies to deepen understanding of the impact of philanthropy within China’s business and social context.